Is depression the contraindication of anterior cervical decompression and fusion for cervical spondylosis? - Chen, Xiaolu; Li, Xiao; Gan, Yu; Lu, Ying; Tian, Yu; Fu, Yixiao; Yang, Hanjie; Liu, Ke; Pan, Yinlian; Du, Xing (Frontiers in Endocrinology, 2022)
Objective: To evaluate whether depression is the contraindication of anterior cervical decompression and fusion (ACDF) for cervical spondylosis. Material and methods: Patients with single-segment cervical spondylosis who underwent ACDF from January 2015 to December 2018 in our department were retrospectively included in this study and divided into two groups. Patients who were diagnosed of depression and prescribed with antidepressant drugs for at least 6 months before surgery were included in the intervention group. Patients without depression were included in the control group. The Beck Depression Inventory (BDI) score was used to evaluate the severity of depression. Visual Analogue Scale (VAS) score, Japanese Orthopeadic Association (JOA) score, Neck Disability Index (NDI), and the 36-Item Short-Form Health Survey (SF-36) were recorded as indexes to assess the pain, cervical spine function, degree of cervical spine injury, and life quality, respectively. The operative time, operative blood loss, hospital stay and complications were also recorded and compared. Results: A total of 117 patients were included in this study, involving 32 patients in the intervention group and 85 patients in the control group. No significant differences were found in operative time, operative blood loss, hospital stay and complications between the two groups (P>0.05). The BDI score, VAS score, JOA score, NDI, SF-36 physical component score (SF-36 PCS) and SF-36 mental component score (SF-36 MCS) were all significantly improved at last follow-up in both the two groups. The intervention group showed higher BDI score and SF-36 MCS than the control group at both preoperative and the last follow-up (P<0.05), and the improvements of BDI score and SF-36 MCS were also higher in the intervention group (P<0.05). Although the intervention group showed higher VAS score, NDI, SF-36 PCS and lower JOA score at preoperative and last follow-up, respectively (P<0.05), there were no significant differences in the improvements of these indexes between the two group (P>0.05). Conclusions: Depression is not the contraindication of ACDF for cervical spondylosis. Depression patients who received preoperative antidepressants can achieve similar improvement of clinical symptoms from ACDF with non-depression patients.